First things first : meeting basic human needs in the developing countries - Streeten, Paul.; Burki, Shahid Javed; World Bank. (New York : Published for the World Bank [by] Oxford University Press, 1981)
In this book, Paul Streeten and his coauthors view the basic needs approach as a logical step in the evolution of economic analysis and development policy and present a clear-sighted interpretation of the issues
Includes index.
Including bibliographical references: p. 193-199.
osa 23/01/2019
Loans
Keywords: Economic assistance; Basic needs; Developing countries